Anti-ischemic and antiarrhythmic effectiveness of long-term bisoprolol therapy in patients with myocardial infarction - R. T. Shukurov; R. D. Kurbanov (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study the effects of long-term bisoprolol (B) therapy on exercise capacity (EC) dynamics, ventricular arrhythmia (VA), and clinical course in patients with myocardial infarction (MI). Material and methods. The study included 114 men with MI (age 30-63 years), receiving long-term B treatment (2,5-10 mg once a day). The parameters assessed included EC dynamics, VA, and clinical course of the disease. Results. Patients with sub-acute MI were characterised by low EC and VA presence, including life-threatening VA forms. Long-term B treatment was associated with a significant reduction in angina attack rate (by 3,9 times) and in the number of nitroglycerin tablets per week (by 4,3 times). In most patients (79,7%), B therapy increased the work performed during stress test (+99%), EC (+43,4%), and exercise time (+52%). In 44 patients (55,7%), an antiarrhythmic effect was observed, including the individuals with high-grade VA (13 out of 15). Long-term B treatment also improved the clinical course of the disease, significantly reducing the end-point rates (in 86,1%). Conclusion. Early started, adequate-dose long-term B therapy improved clinical course of the disease and demonstrated good anti-ischemic, antianginal, and antiarrhythmic effects in MI patients, including those with life-threatening VA forms.